Mythological transformations in the poem "The Tyger" by William Blake and the cycle "There Was a Tiger Here" by Gregor Strniša - Živković, Dušan (Primerjalna književnost, 2020)
This article provides an analysis of the background, processes and functions of mythological transformations found in the poem "The tiger" by William Blake and the cycle of poems " There as a tiger here" ("Tu je bil tiger") by Gregor Strniša. It elaborates on the various levels of analogies between the poetic and semantic aspects on the creation of mythopoetic world, along with the specificities revealed in the relations between Blake's romantic visions and Strniša's modern perspectives, in the domains for the following aspects: 1. General poetic features; 2. The analysis of symbolic systems; 3. The nature and functions of spatio-temporal relations; 4. The significance of an image of a tiger in the quest for gaining knowledge of divine thought, eternity, transience and death. Therefore, apart from placing emphasis on the significance of Blake's mystical tendencies, the purpose of this work is to demonstrate that the poetry of Gregor Strniša is ranked among the world's greatest literature, considering the fact that it is perceived as an original poetic vision which has contributed to the creation of innovations in the context of modern mythological transformations.
Keywords: angleška poezija; Blake, William; mitološke preobrazbe; mitopoetika; slovenska poezija; Strniša, Gregor; tiger; živalski liki